Music therapy research and evidence-based practice. - Yinger, Olivia Swedberg; Yinger, Olivia Swedberg (St. Louis, Missouri Elsevier, 2018)
Get a quick, expert overview of the clinical and evidence-based use of music interventions in health care. This practical resource compiled by Dr. Olivia Swedberg Yinger provides a concise, useful overview of the profession of music therapy, including a description of each of the research-support practices that occur in the settings where music therapists most commonly work.
Foreword / Jayne M. Standley -- Author's preface / Olivia Swedberg Yinger -- Overview of the music therapy profession / Olivia Swedberg Yinger -- Neurologic foundations of music-based interventions / Kimberly Sena Moore -- Music therapy in educational settings / Michael R. Detmer -- Music therapy in mental health treatment / Lori F. Gooding -- Music therapy in medical treatment and rehabilitation / Darcy DeLoach -- Music therapy in hospice and palliative care / Meganne K. Masko -- Music therapy in gerontology / Olivia Swedberg Yinger -- Music therapy and wellness / Lorna E. Segall -- Current trends and future directions in music therapy / Alejandra J. Ferrer.
Includes bibliographical references and index.
Keywords: Music therapy; Music Therapy -- methods; Evidence-Based Practice